2017
DOI: 10.1016/j.jmoldx.2016.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Gene Expression Test for Mesothelioma Prognosis in Formalin-Fixed Paraffin-Embedded Tissues

Abstract: A molecular test performed using fresh-frozen tissue was proposed for use in the prognosis of patients with pleural mesothelioma. The accuracy of the test and its properties was assessed under Clinical Laboratory Improvement Amendmentseapproved guidelines using FFPE tissue from an independent multicenter patient cohort. Concordance studies were performed using matched frozen and FFPE mesothelioma samples. The prognostic value of the test was evaluated in an independent validation cohort of 73 mesothelioma pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…The test demonstrates high repeatability and reproducibility, successfully discriminating high and low risk patients based on outcomes following surgery-based therapy. Importantly, the test was further validated using formalin-fixed paraffinembedded tissue samples, which supports its applicability to routinely collected clinical material (24). In addition, recent RNA-Seq profiling of over two hundred MPM tumors led to identification of distinct molecular clusters that align approximately with tumor histology, reflect gene expression signatures indicative of epithelial to mesenchymal transition and stratify survival (25).…”
Section: Review Articlementioning
confidence: 66%
“…The test demonstrates high repeatability and reproducibility, successfully discriminating high and low risk patients based on outcomes following surgery-based therapy. Importantly, the test was further validated using formalin-fixed paraffinembedded tissue samples, which supports its applicability to routinely collected clinical material (24). In addition, recent RNA-Seq profiling of over two hundred MPM tumors led to identification of distinct molecular clusters that align approximately with tumor histology, reflect gene expression signatures indicative of epithelial to mesenchymal transition and stratify survival (25).…”
Section: Review Articlementioning
confidence: 66%
“…To analyse gene expression profiles of our samples, we used a targeted whole transcriptome sequencing approach reported as highly accurate and perfectly comparable with RNA-sequencing approaches and next generation sequencing platforms utilized to obtain TCGA data 16 . Although TCGA samples are fresh frozen and we analysed only formalin-fixed and paraffin-embedded (FFPE) tissues, the comparison of transcriptome data is supported by several evidences demonstrating a high correlation of gene expression profiles between these two types of specimens 1719 . Anyway, in order to overcome this potential limitation, a validation of results was carried out on an independent cohort of PSC, LUAD and LUSC FFPE tissues from our archives.…”
Section: Discussionmentioning
confidence: 94%
“…De Rienzo et al . discuss the use of a gene expression test to determine the prognosis of patients with mesothelioma using samples taken prior to surgery . When comparing their data to an independent cohort, they found that the gene expression score was a significant predictor of survival in both univariate and multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%